Bioinformatics and experimental findings reveal the therapeutic actions and targets of pachymic acid against cystitis glandularis. (24th April 2021) - Feng, Zihao; Shi, Hailin; Liang, Bojian; Ge, Tianyu; Cai, Menghui; Liu, Feng; Huang, Kunping; Wen, Jintao; Chen, Qiuhong; Ge, Bo
Abstract: Pachymic acid (PA), a bioactive ingredient isolated from Poria cocos Wolf, is reported with potential benefits of anti‐inflammatory, anti‐oxidative actions. It is reasoned that PA may play the potential benefits against cystitis glandularis (CG), an inflammation of the bladder tissue. In this study, we aimed to apply the network pharmacology and molecular docking analyses to reveal concrete anti‐CG targets and mechanisms of PA, and then the bioinformatic findings were verified by using clinical and animal samples. The methodological data from network pharmacology approach showed that 303 and 243 reporting targets of CG and PA, and other 31 shared targets of CG and PA were identified. Subsequently, all top targets of PA against CG were screened out, including cyclooxygenase‐2, epidermal growth factor receptor, tumor antigen p53 (TP53), tumor necrosis factor‐alpha (TNF), interleukin‐1 (IL‐1) beta, proto‐oncogene c‐jun. Molecular docking data demonstrated that PA exerted potent bonding capacities with TNF, TP53 proteins in CG. In human study, the findings suggested that overactivated TNF‐α expression and suppressed TP53 activation were detected in CG samples. In animal study, PA‐treated mice showed reduced intravesical IL‐1, IL‐6 levels, and lactate dehydrogenase content, downregulated TNF‐α and upregulated TP53 proteins in bladder samples. Taken together, our bioinformatics and experimental findings identify the key anti‐CG biotargets and mechanisms of PA. More markedly, these pivotal pharmacological targets of PA against CG have been screened out and verified by using computational and experimental analyses.